THE UNIVERSITY OF WISCONSIN-MADISON’S MASTER OF ENGINEERING IN PROFESSIONAL PRACTICE (MEPP) PROGRAM: THE ROAD TO QUALITY ONLINE GRADUATE ENGINEERING EDUCATION - Wayne P. Pferdehirt; Thomas W. Smith; Karen R. Al-Ashkar (Online Learning, 2019)
This case study explores several key design strategies behind the University of Wisconsin-Madison’s Master of Engineering in Professional Practice (MEPP) program. Since its full-scale launch in 1999, this demanding graduate engineering degree program has achieved a graduation rate of more than 99% and has received major awards for instructional quality from the Sloan Consortium, the U.S. Distance Learning Association, and the University Continuing Education Association. This paper examines several key elements of the program’s design and practical lessons learned through the program’s first six years, during which 140 students have graduated from the two-year degree program. Distinctive elements of the program include: the program’s cohort design; integration of weekly Webconferencing with asynchronous Web-based tools; optimization of course content and format for experienced, mid-career adults; and an annual on-campus residency. Program details are available at http://mepp.engr.wisc.edu.